A novel infrared thermography technique for measuring heat transfer in transonic turbine blades - Sisti, M (2024)

(untitled)
This thesis presents a new measurement methodology aimed at accelerating progress in the Aviation industry while ensuring reliable results. A novel measurement system employing Infrared (IR) Thermography was developed for the Oxford Turbine Research Facility (OTRF), a national engine-representative high-pressure turbine test facility operating with rotational speed of 300 m s−1 and transonic flow.